PENGAWASAN MAJELIS PENGAWAS DAERAH TERHADAP NOTARIS DI KABUPATEN INDRAMAYU - , TRI MEITASARI BAKHTIAR ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purposes of this research are : 1) to know the control by district monitoring council toward notary in Indramayu regency, 2) to know the difficulties that have been faced by district monitoring council in controlling notary in Indramayu regency, and 3) to know the district monitoring council efforts in increasing the control. The research used juridical empirical as the method. This research was conducted through direct interview with respondents and also supported with secondary data. Sampling techniques was non probability sampling by using purposive sampling. The data were analyzed qualitatively and the result of that analysis was presented descriptively. The research results show that the control by district monitoring council has not been maximal and total. Inspection being made is not conducted regularly. The inspection team is only checking the protocol book. The inspection is just formality. The difficulties being faced by district monitoring council are : (a) managing time to meet with another members of district monitoring council